Effect of Aerobic Exercise on Psychological Problems of Female Students with Premenstrual Syndrome in Imo State, Nigeria - Jane Ekwutosi Iheka (Universal Journal of Educational Research)
The psychological problems of students with premenstrual syndrome hampers not just their wellbeing but their willingness to commit to education due to emotional instabilities associated with their condition. It is in line with the obvious need to proffer solution that this study examined the effect of aerobic exercise on psychological problems of female students with premenstrual syndrome in Imo state using a quasi-experimental design. The population comprised 96 female students which served as the sample size due to its number being manageable after meeting the inclusion criteria. A Premenstrual Symptom Screening Tool (PSST) was used to diagnose Premenstrual Syndrome among the participants. A self-constructed instrument titled ‘Students Psychological Problems Scale’ (SPPS) with 20 items was utilized for the study. The researcher presented the instrument to specialists in Educational Psychology and Measurement and Evaluation who validated it. Also, its reliability was established as .81 using Cronbach alpha statistics to ascertain its internal consistency. The research questions were answered using Mean and standard deviation while hypotheses were tested at .05 level of significance using paired t-test. The result of the study showed a significant mean difference (11.82) on anxiety level, and a significant mean difference (10.82) on depression level of students with premenstrual syndrome before and after the aerobic exercise. Therefore, aerobic exercise was found effective in reducing psychological problems (anxiety and depression) among female students with premenstrual syndrome. From the findings, the researcher recommended among others that physical exercise should be observed in schools to improve the wellbeing of students with psychological problems.